Health and Healing in Minority Religions - Harvey, Sarah (Routledge Inform Series on Minority Religions and Spiritual Movements Series, 2025)
This volume explores the diversity of beliefs and practices around health and healing in minority religions from different perspectives. The contributors include academics from a variety of disciplines as well as members of minority religions.